Cis-acting sequences regulating expression of the human alpha-globin cluster lie within constitutively open chromatin. - Vyas, P; Vickers, M; Simmons, D; Ayyub, H; Craddock, C; Higgs, D (1992)
Current models suggest that tissue-specific genes are arranged in discrete, independently controlled segments of chromatin referred to as regulatory domains. Transition from a closed to open chromatin structure may be an important step in the regulation of gene expression. To determine whether the human alpha-globin cluster, like the beta-globin cluster, lies within a discrete, erythroid-specific domain, we have examined the long-range genomic organization and chromatin structure around this region. The alpha genes lie adjacent to at least four widely expressed genes. The major alpha-globin regulatory element lies 40 kb away from the cluster within an intron of one of these genes. Therefore, unlike the beta cluster, cis-acting sequences controlling alpha gene expression are dispersed within a region of chromatin that is open in both erythroid and nonerythroid cells. This implies a difference in the hierarchical control of alpha- and beta-globin expression.